Jenis, Strategi, dan Fungsi Tindak Tutur dalam Wawancara oleh Tokoh yang Sedang Menjadi Pusat Perhatian Publik - Rosendra, Nayatri Putri; Manaf, Ngusman Abdul (Persona: Kajian Bahasa dan Sastra, 2024)
This study aims to identify and describe the types, strategies, and functions of speech acts in interviews conducted with public figures who are currently in the spotlight. This research is descriptive in nature, employing both qualitative and quantitative approaches. The data consists of utterances from three prominent figures who are currently the focus of public attention. The source of the data is interview videos from the "Mata Najwa" talk show. The methods and techniques used for data collection include the observation method with the nonparticipatory observation technique. Data validation was conducted using triangulation techniques. The findings of this study are as follows. First, five types of speech acts were identified: (1) assertive speech acts, (2) directive speech acts, (3) expressive speech acts, (4) commissive speech acts, and (5) declarative speech acts. The most dominant types of speech acts used were assertive and directive speech acts, indicating that the speakers, being the interviewees, provided many responses and explanations. Second, four speaking strategies were identified: (1) speaking directly without preamble, (2) speaking directly with positive politeness strategies, (3) speaking directly with negative politeness strategies, and (4) speaking ambiguously. The most dominant speaking strategies used were speaking directly without preamble and speaking directly with positive politeness strategies, indicating that the speakers aimed to communicate politely and respectfully with their interlocutors. Third, four functions of speech acts were identified: (1) competitive, (2) convivial, (3) collaborative, and (4) conflictive. The most dominant speech act functions used were collaborative and convivial, indicating that the speakers aimed to communicate optimistically while still considering social goals